1997
DOI: 10.1007/s002679900011
|View full text |Cite
|
Sign up to set email alerts
|

Toleration of Traffic by Vegetation: Life Form Conclusions and Summary Extracts from a Comprehensive Data Base

Abstract: / An exhaustive search of the literature for foot and vehicle traffic impacts on vegetation has yielded more than 400 citations, two thirds of which held sufficient detail to be usefully distilled into a personal-computer data base. A total of 1444 individual observations involving 737 species that were trampled are included. Compromises were made in the depth of entry detail and to allow comparability among data. Inconsistent, generally short-term, experimental practices disallowed formal statistical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
6

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 29 publications
3
78
0
6
Order By: Relevance
“…One reason could be that the vegetation community at SRNP had the highest proportion of grasses and non-living material relative to the other two national parks. Previous studies have indicated that the grass life form is more resistant and resilient to trampling than shrub life forms (Sun and Liddle 1993c;Liddle 1997;Yorks et al 1997;Whinam and Chilcott 1999;Hill and Pickering 2009). …”
Section: Resistance Index (Vegetation Cover)mentioning
confidence: 99%
See 1 more Smart Citation
“…One reason could be that the vegetation community at SRNP had the highest proportion of grasses and non-living material relative to the other two national parks. Previous studies have indicated that the grass life form is more resistant and resilient to trampling than shrub life forms (Sun and Liddle 1993c;Liddle 1997;Yorks et al 1997;Whinam and Chilcott 1999;Hill and Pickering 2009). …”
Section: Resistance Index (Vegetation Cover)mentioning
confidence: 99%
“…In this study the slow or absence of growth of dominant plant genera (Hakea, Acacia, Banksia, Melaleuca, Leucopogon and Verticordia) (Table 2) evident over a 12-month period thus relates to the propensity for plant growth to be naturally limited by the availability of water and nutrients (e.g. Yorks et al 1997;Specht and Specht 1999;Hopper and Gioia 2004). Malmivaara-Lamsa et al (2008) found that in Finland the tolerance (combining resistance and resilience) of vegetation increased with fertility of the soil.…”
Section: Resilience (Recovery) Of Vegetation (Cover and Height) To Trmentioning
confidence: 99%
“…Trampling may increase mortality and reduce recruitment of seedlings and small saplings, biasing estimates of population dynamic rates. In addition, because species differ in their ability to tolerate and recover from physical damage (Boucher et al 1991;Ickes et al 2003;Yorks et al 1997), trampling by researchers could potentially cause shifts in the structure and composition of vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Uma das questões que mais preocupam em relação aos impactos da visitação sobre as áreas naturais e que tem sido alvo de numerosos estudos diz respeito dos efeitos do pisoteio humano sobre a vegetação (COLE, 1995aLIDDLE, 1991, 1993a, YORKS et al, 1997.…”
Section: Iv1 Introduçãounclassified
“…Muitos dos trabalhos em Ecologia da Recreação dos últimos anos vêm tratando de indicar quais espécies são capazes de sobreviver em áreas impactadas pelo pisoteio, quais espécies recuperam melhor e por que umas espécies resistem e/ou recuperam melhor do que outras (LIDDLE, 1991;YORKS et al, 1997).…”
Section: Iv1 Introduçãounclassified